A new joint-slippage model for galvanized steel bolted joints with slippage. (December 2021) - Li, Benben; Zhan, Yang
Abstract: This paper presents a new joint-slippage model for determining the behavior of galvanized steel bolted joints with slippage based on the joint test results. The influence of the slip coefficient of the friction surface is considered in the new model. Validation of the new joint-slippage model is performed in terms of test results of full-size galvanized latticed steel girders. In addition, by comparison with the conventional rigid joint model and the most representative joint-slippage model – Ungkurupanian's joint-slippage model, the new joint-slippage model exhibits the best performance according to predicted structural deflection, stiffness and ultimate bearing capacity. The effect of slip coefficient on the behavior of the new joint-slippage model and Ungkurupanian's joint-slippage model is further discussed through structural response. The new model can be easily embedded into finite element analysis software and has the potential to be used in the design stage for accurately assessing the safety and reliability of galvanized steel structures.